1999
DOI: 10.1255/ejms.290
|View full text |Cite
|
Sign up to set email alerts
|

Generation of three isomers of C7H– in the gas phase. A joint experimental and theoretical study

Abstract: Three anion isomers of formula C 7 H have been synthesised in the mass spectrometer by unequivocal routes. The structures of the isomers are [HCCC(C 2) 2 ]-, C 6 CH and C 2 CHC 4-. One of these, [HCCC(C 2) 2 ]-, is formed in sufficient yield to allow it to be charge stripped to the corresponding neutral radical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 51 publications
(71 reference statements)
0
7
1
Order By: Relevance
“…In these experiments, C n H -, where n is even, were generated in a pulsed discharge of acetylene (HC;CH) and carbon dioxide in neon (Taylor et al 1998), whilst C 3 Hwas produced from allene (H 2 C¼C¼CH 2 ) and molecular oxygen in a Branscomb discharge source (Oakes & Ellison 1986). Gas-phase preparation of C 3 H -, C 5 Hand C 7 Hin a mass spectrometer has also been reported (Dua, Bowie & Sheldon 1994;Blanksby et al 1997;Dua, Bowie & Blanksby 1999). These procedures are outlined in Scheme 1 and involve (a) deprotonation of a synthesized polyacetylide precursor in the gas phase, followed by (b) decomposition of the parent anion.…”
Section: N H Anionsmentioning
confidence: 85%
See 1 more Smart Citation
“…In these experiments, C n H -, where n is even, were generated in a pulsed discharge of acetylene (HC;CH) and carbon dioxide in neon (Taylor et al 1998), whilst C 3 Hwas produced from allene (H 2 C¼C¼CH 2 ) and molecular oxygen in a Branscomb discharge source (Oakes & Ellison 1986). Gas-phase preparation of C 3 H -, C 5 Hand C 7 Hin a mass spectrometer has also been reported (Dua, Bowie & Sheldon 1994;Blanksby et al 1997;Dua, Bowie & Blanksby 1999). These procedures are outlined in Scheme 1 and involve (a) deprotonation of a synthesized polyacetylide precursor in the gas phase, followed by (b) decomposition of the parent anion.…”
Section: N H Anionsmentioning
confidence: 85%
“…1996) or in a Branscomb ion source (Oakes & Ellison 1986). Gas‐phase preparation of C 3 O – , C 5 O – and C 7 O – in a mass spectrometer has also been reported (Blanksby , Dua & Bowie 1999a; Dua, Blanksby & Bowie 2000a,b). These procedures are outlined in Scheme 5 and involve (a) deprotonation of a synthesized polyacetylide precursor in the gas phase, followed by (b) decomposition of the parent anion.…”
Section: Trends In the Physical Properties With Increasing Chain Lementioning
confidence: 98%
“…Dua et al 91 have observed that electron capture by tetracyanoethylene oxide can promote the reaction…”
Section: Some Reactions and Unusual Anion States In The Gas Phasementioning
confidence: 99%
“…For C 5 H À and C 7 H À , several low-lying isomers with singlet and triplet spin multiplicity have been previously reported. 16,46,53 The carbon backbone of these isomers can be a single chain, a branched chain, or a branched three-membered ring. Consequently, we searched for the lowest energy isomers of C 5 H À , C 7 H À and C 9 H À by performing electronic structure calculations at the B3LYP/6-311+G level of theory on several different initial geometries for both the singlet and triplet surfaces.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Using these energetics and PE spectroscopy, Sheehan et al 16 recently suggested that a cyclic isomer was the lowest energy structure for the C 5 H À anion. Bowie and coworkers 46,53 have also reported the synthesis of several anionic and neutral isomers of C 5 H and C 7 H using mass spectrometry techniques and precursors with the proper bond connectivity.…”
Section: Introductionmentioning
confidence: 99%